Journey through ramadan – a diabetes in ramadan patient education program - Mohamed Shah, Fatimah Zaherah; Eddy Warman, Nur 'Aini (Faculty of Medicine, 2023)
The incidence of Type 2 Diabetes Mellitus (DM) in Malaysia is increasing, with an estimated almost 4 million adults diagnosed, according to the Malaysian National Health and Morbidity Survey (NHMS) 2019. This is primarily contributed by the Malay race, with a prevalence of 59%, followed by the other races, translating into a large population of people with diabetes who will be fasting during the month of Ramadhan in this country. Fasting in Ramadhan for those with diabetes mellitus is challenging and needs close monitoring with sufficient and comprehensive medical advice.